Implementasi New Publik Manajemen dalam Peningkatan Kualitas Pelayanan di Rumah Sakit (RST) dr. Reksodiwiryo Padang - Adnan, Fachri; Sinaga, Alahan; Rizki Ananda, Bobi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The existence of bad services carried out by various hospitals in the area. So that there are people who complain about the health service The purpose of this study was to determine the implementation of excellent service for patients who use the Social Security Administration Agency (BPJS) in the Inpatient Unit of Dr. Army Hospital. Reksodiwiryo Padang.. This study uses qualitative research methods with data collection techniques through interviews, observation and documentation. Informants come from the hospital and the community who provide services. As for the results of this study, users show that excellent service for BPJS patients at RST Dr. Reksodiwiryo Padang has been running well with the existing Service Operational Standards (SOP) foundation. It's just that there are some obstacles found such as the path that is too long for the patient to go through, the lack of control over household facilities.